Flexural-strengthening efficiency of cfrp sheets for unbonded post-tensioned concrete T-beams - Nguyen-Minh, L.; Phan-Vu, P.; Tran-Thanh, D.; Phuong Thi Truong, Q.; Pham, Thong; Ngo-Huu, C.; Rovnák, M. (Pergamon, 2018)
There has been a limited number of studies about the flexural behavior of unbonded post-tensioned concrete (UPC) beams strengthened with carbon fibre reinforced polymer (CFRP) and these studies have not systematically examined the effect of CFRP sheets on the tendon strain as well as the strengthening efficiency. Moreover, current design guides for the FRP strengthening techniques have not provided any design procedure for UPC structures. This study, thus, investigates the influence of CFRP sheet ratio on the flexural behavior of CFRP-strengthened UPC T-beams and quantifies its effect upon tendon behavior in this kind of UPC beams. The testing program consisted of nine large-scale UPC T-beams strengthened by different layers of CFRP sheets with or without CFRP U-wrapped anchors. The experimental results have shown that the use of CFRP sheets and CFRP U-wrapped anchors significantly affected the tendon strain. The FRP reinforcement ratio governed the flexural capacity, the crack width, the mid-span displacement, and the ductility of the beams in which the strengthening efficiency reduces with the increased number of CFRP layers. The configuration of the CFRP U-wrapped anchors affected the strain of the CFRP sheets, the failure mode and thus the beam behavior. In addition, semi-empirical equations were proposed to estimate the actual strain of unbonded tendons in which the effect of the CFRP sheets and CFRP U-wrapped anchors have been taken into consideration. The proposed equations, which are simple to use, yield reliable predictions with a small variation.